PENGARUH HALAL AWARENESS, SOCIAL MEDIA MARKETING, DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG WISATAWAN MUSLIM KE DESTINASI WISATA RAMAH MUSLIM DI JAWA TIMUR - Bagas Adiyaksa Wibawa; Ach. Yasin (STKIP Subang, 2026)
This study analyzes the effect of Halal Awareness, Social Media Marketing, and Destination Image on Muslim tourists' visit intention toward Muslim-friendly tourism destinations in East Java, a province with a large Muslim population and considerable but not yet optimally developed halal-tourism potential. A quantitative associative approach was employed through an online survey (Google Form) using a Likert scale, distributed to Muslim tourists selected through purposive sampling. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS, covering outer model testing (convergent and discriminant validity, reliability), inner model testing (collinearity, R-square, Q-square, F-square), and hypothesis testing via bootstrapping. The results show that Halal Awareness and Destination Image each have a significant positive effect on visit intention, while Social Media Marketing has no significant direct effect. The three variables jointly contribute to explaining visit intention, though a considerable share of its variance remains unexplained by the model. These findings indicate that Muslim tourists' decisions are primarily value-driven, guided by halal awareness and destination image, while social media functions only as a complementary information channel rather than a direct determinant of visit intention. The study recommends that destination managers and local governments strengthen halal facility development, reinforce destination branding as Muslim-friendly, and redesign social media content to explicitly highlight halal attributes.